THE NEWEST ACHIEVEMENTS OF PHARMACEUTICAL DEVELOPMENT BASED ON THE USE OF COLLAGEN - M. M. Karasev; M. A. Redina; O. V. Belousova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The work is devoted to the review of the application of collagen and materials based on collagen in medicine and the pharmaceutical industry. We have taken into consideration the aspects of the use of "Collost" sterile bioplastic collagen material in surgery and options for further research areas of biomaterials on the basis of unreconstructed collagen.